Social representations of nurses of the Emergency Care Unit towards people with mental disorder* - Sabeh, Anna Carla Bento; Cecilio, Hellen Pollyanna Mantelo; Campos, Claudinei José Gomes; Reis, Helca Franciolli Teixeira; Wysocki, Anneliese Domingues; Santos, Edirlei Machado dos (Revista da Escola de Enfermagem da USP, 2023)
Objective: To understand the Social Representations of nurses from an Emergency Care Unit about the care provided to people with mental disorders. Method: Qualitative exploratory study, supported by the theoretical and methodological framework of the Theory of Social Representations. Interviews were conducted from July to August 2021. The data were processed using the IRaMuTeQ software. Results: 22 nurses were interviewed. From the processed data, three discursive categories were constructed: the tortuousness of the Psycho-Social Care Network (RAPs): in search of a path; the abyss between the health professional and the person with mental disorder; and unveiling the care of nurses in the Mental Health Emergency Care Unit. Conclusion: We identified a lack of knowledge about the Psychosocial Care Network, anchoring elements associated with previous negative experiences that influence the professional-patient relationship, and nursing care permeated by cognitive barriers. Such findings are unprecedented in the locality studied and relevant to promote the qualification of the work of nurses in mental health in the Emergency Care Unit.